Improving the Students’ Reading Skill trough Note-Taking Technique: A Pre-Experimental Research - Nurmila (Newinera Publisher, 2020)
This research aimed at finding out the improvement of the students’ critical comprehension and creative comprehension. The researcher applied a pre-experimental design. The sample was taken by a total sampling technique and the total number of samples was 20 students. It employed eight meetings (one meeting for pre-test, six meetings for treatment, and one meeting for post-test). It employed a reading test as an instrument. The results of this research showed that the Note-Taking Technique improved students’ reading skill which focused on critics and creativity. It was proved by the students’ post-test score that was higher than the students’ pre-test score. It also proved by the value of the t-test 6.29, which was higher than the value of t- table 2.093. This indicated that the alternative hypothesis was accepted, and the null hypothesis was rejected and there was a significant difference in the students’ reading skill before and after using Note-Taking Technique. It was concluded that the use of Note-Taking Technique can improve the students’ reading skill.